2022
DOI: 10.1016/j.jenvp.2021.101747
|View full text |Cite
|
Sign up to set email alerts
|

Space at home and psychological distress during the Covid-19 lockdown in Italy

Abstract: Prolonged periods of restrictions on people's freedom of movement during the first massive wave of the COVID-19 pandemic meant that most people engaged in all their daily activities at home. This suggested the need for the spatial features of the home and its occupants' perception of them to be investigated in terms of people's wellbeing. The present study was conducted on a large sample (N = 1354) drawn from different Italian regions. It examined the relationship between the “objective” and “subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 72 publications
(103 reference statements)
4
17
0
4
Order By: Relevance
“…According to the hypothesis proposed by Cutrona et al ( 14 ), the environmental variable increases depression, with everyday stress as a mediator ( 14 ). Furthermore, previous studies support the significant relationships between residential environment satisfaction and stress ( 15 , 16 ) as well as between stress and depression ( 17 , 18 ).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…According to the hypothesis proposed by Cutrona et al ( 14 ), the environmental variable increases depression, with everyday stress as a mediator ( 14 ). Furthermore, previous studies support the significant relationships between residential environment satisfaction and stress ( 15 , 16 ) as well as between stress and depression ( 17 , 18 ).…”
Section: Introductionsupporting
confidence: 61%
“…Also, students with low levels of satisfaction with their social and psychological residential environment were more perceptive to environmental stress. Fornara et al ( 16 ) indicated that satisfaction with the space at home has a significant effect on perceived stress ( 15 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This measure is widely used (e.g., Torshizian & Grimes, 2020 ). However, some recent studies have shown that subjective indices related to feeling too close to others (e.g., Fornara et al, 2022 ; Thornock et al, 2019 ) may have even higher predictive power than the objective measures. Therefore, our results on the relationship between household crowding and support for anti-democratic political systems may actually underestimate the true relationship between the two variables.…”
Section: Discussionmentioning
confidence: 96%
“…A vida pública e a privada se misturaram novamente, passando a coexistir em um (BRANT, 2020;YANG, et al, 2021). Ainda que a pandemia tenha afetado diversos setores da vida, a prática forçada do trabalho em casa foi uma das mais significativas, pois trouxe grandes desafios tanto para as organizações quanto para os funcionários e seus familiares (FORNARA et al, 2021).…”
Section: O Teletrabalho Em Tempos De Pandemiaunclassified
“…Nessa perspectiva, a casa passou a ser o centro das atenções pois tornou-se o principal refúgio para uma grande parcela da população (FORNARA et al,2021). Tal fato, significou uma sobreposição de funções no ambiente doméstico, visto que as atividades relacionadas ao trabalho que antes eram realizadas em escritórios ou empresas foram transferidas para dentro da residência (BONENBERG;LUCCHINI ,2020).…”
Section: Introductionunclassified